2022
DOI: 10.1186/s10195-022-00630-1
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma (PRP) augmentation does not result in more favourable outcomes in arthroscopic meniscal repair: a meta-analysis

Abstract: Background The efficacy and safety of platelet-rich plasma (PRP) augmentation for arthroscopic meniscal repair is controversial. This meta-analysis compared arthroscopic meniscal repair performed in isolation or augmented with PRP. Methods The present study was conducted according to PRISMA 2020 guidelines. Pubmed, Web of Science, Google Scholar and Embase were accessed in August 2021. All the clinical trials which compared arthroscopic meniscal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…Finally, the use of hyaluronic acid did not produce any clinical benefit in either group. The inefficacy of intraarticular infiltrations in APM, such as hyaluronic acid and/or platelet rich plasma (PRP), is also supported by previous evidence [5, 12, 13, 15, 20, 28, 29, 32, 38, 45]. Berg et.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Finally, the use of hyaluronic acid did not produce any clinical benefit in either group. The inefficacy of intraarticular infiltrations in APM, such as hyaluronic acid and/or platelet rich plasma (PRP), is also supported by previous evidence [5, 12, 13, 15, 20, 28, 29, 32, 38, 45]. Berg et.…”
Section: Discussionsupporting
confidence: 54%
“…Degenerative meniscal damage is common in adults [ 14 , 27 ]. At present, the optimal management for non-traumatic, degenerative meniscal damage remains controversial [ 8 , 38 ]. Meniscal tears are defined as intrameniscal linear signal penetrating one or both surfaces of the meniscus at magnetic resonance imaging (MRI) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the forest plots demonstrated that the failure rate of meniscus repair treatment in the PRP group improved significantly compared with that in the non-PRP group. Although a recent meta-analysis on the application of PRP in arthroscopic meniscus repair showed no significant difference in the failure rate [ 43 ], only three studies on the failure rate were included [ 19 , 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Studies evaluating PRP for augmentation of meniscus repair have reported variable outcomes, with some studies reporting improved healing 10,11 while other studies report no effect. 12 PRP has also been evaluated for augmentation of anterior cruciate ligament (ACL) graft healing in a bone tunnel and to improve ACL graft maturation and remodeling; however, most studies have not reported a positive effect. 13 A summary of AAOS Clinical Practice Guidelines related to orthobiologics is presented in Table 1.…”
Section: Platelet-rich Plasmamentioning
confidence: 99%